Challenging Practice: an approach to Cooperative Analysis - Mogensen, Preben Holst (DAIMI Report Series, 1994)
Cooperative Analysis takes as its starting point the tradition of user-involvement in system development in Scandinavia, especially cooperative design. It points to the mismatch in this tradition between analysis as passive observation and design as cooperative intervention. Cooperative Analysis is conducted cooperatively and through intervention in the practice beeing analysed. Cooperative Analysis is seen as part of a large development process, and is thus seen as facilitating taking action in order to bring about change. The primary approach is one of provoking current practice through concrete experience. Provocation serves the purpose of calling forth hitherto taken-for-granted issues as well as it challenges the existing practice to investigate its dynamics and open up for new possibilities. As two specific means to this end, the book introduces an approach of using artifacts (e.g. commercially available products, prototypes, and mock-ups) to trigger new understandings of current practice and it introduces dilemma games to challenge current practice by exposing it to some of its inherent dilemmas.